Análise da voz e do comportamento do trato vocal suplaglótico por meio visual, perceptivo-auditivo e acústico em mulheres disfônicas com diferentes configurações glóticas - Nunes, Raquel Buzelin (2005)
Objective: To analyze voice and supraglottic vocal tract using imaging of the vocal tract, perceptual and acoustic methods in dysphonic women with different glottic configurations. Method: The studied sample comprised 31 women, aged 20 to 45 years, with vocal complaints and affections. Subjects underwent brief assessment of sensorial-motor-oral system, videolaryngostroboscopy and nasofibrolaryngoscopy, and vocal recording. First of all, the otorrinolaryngologist reviewed the medical results and selected exams that presented similar laryngeal affections, forming three distinct groups (bilateral nodules, mucosa cover damage and chinks). A VHS tape was edited with nasofibrolaryngoscopic exams for visual analysis of the vocal tract and a CD with the voices was edited for perceptual and acoustic analysis. Visual analysis was jointly carried out by three speech therapists and three otorrinolaryngologists that checked the following parameters: supraglottic constriction, vertical laryngeal mobility, pharyngeal constriction and tongue mobility. Perceptual analysis was carried out by the same speech therapists using the Vocal Profile Analysis Scheme (VPAS) and assessment of parameters of pitch, loudness and resonance. Values of the frequency of formants were extracted from CSL software (Kay Elemetrics). Data from visual, perceptual and acoustic analyses were statistically analyzed. Results: The results of the visual analysis did not show statistically significant differences that could distinguish the groups. Thus, the results were described for a total group of 31 subjects. Out of the analyzed parameters, we noticed that supraglottic constriction was present in 21 subjects. Laryngeal vertical mobility was average in 12 subjects and restricted in 16. Sixteen subjects presented pharyngeal constriction - nine were circular, seven were lateral. The position of the tongue remained neutral in 27 subjects. Analysis of vocal quality using VPAS revealed that the following findings were the most predominant: high larynx position, labial-dental position, stretched lips, closed mandible, advanced tip of the tongue, and phonation adjustments of breathiness, harsh voice and hyperfunction. Cluster factor analysis showed that supraglottic adjustments were determinant for the characterization of vocal quality. The pitch ranged from low and medium to low in 28 analyzed subjects. Loudness level was high in 23 subjects and resonance was low in 20 subjects. In the acoustic analysis, values of formants were within the normal reference range. Conclusion: Vocal quality is not exclusively related with specific glottic affection, but rather with behaviors of the whole vocal tract, evidencing the need to consider supraglottic adjustments in the characterization of vocal quality of dysphonic subjects